STRATEGI PEMBELAJARAN MAHARAH AL KALAM BAGI SANTRI PONDOK PESANTREN AL FATH CILEGON - Ahmad Erssad Al Bai Suni; Maulidin, Syarif; Kurniawan, Wakib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies used in teaching maharah al-kalam for students at Pondok Pesantren Al Fath Cilegon. Speaking skill is one of the most important competencies in Arabic language learning because it supports students in communicating actively and understanding Arabic in daily activities. However, many students still face difficulties in speaking Arabic due to limited vocabulary mastery, low self-confidence, and lack of language practice outside the classroom. This research employed a qualitative descriptive approach with a field research design. Data were collected through observation, in-depth interviews, and documentation involving Arabic teachers and ten students at Pondok Pesantren Al Fath Cilegon. The results of the study indicate that the learning strategies applied include direct methods, daily conversation practices (muhadatsah), vocabulary memorization (mufradat), speech activities (muhadharah), and the implementation of bi’ah lughawiyah as an Arabic-speaking environment. These strategies were found to improve students’ speaking abilities, increase vocabulary mastery, and enhance students’ confidence in communicating using Arabic. Supporting factors in the learning process include teacher guidance, language habituation, and a conducive learning environment, while the main obstacles include differences in students’ abilities and limited vocabulary mastery. The study concludes that communicative learning strategies combined with a supportive language environment can significantly improve students’ maharah al-kalam.